Ethnochemistry: Potential, Implementation, and Challenges of Integrating Local Wisdom to Enhance Student Motivation and Engagement - Almur, Faathir; Agussalim, Hastuti (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Chemistry is often perceived as an abstract and challenging subject, leading to low student motivation and engagement. This article aims to investigate the role of ethnochemistry, integration of local wisdom into chemistry instruction as an innovative approach to address this issue. A thematic literatur review was conducted by analyzing 10 articles from indexed national and international journals (Google Scholar, Scopus, SINTA) published between 2015 and 2025. The findings reveal that ethnochemistry has been implemented through diverse cultural contexts, such as batik-making, traditional food fermentation, and the use of medicinal plants, which are linked to core chemistry concepts (e.g., redox reactions and chemical bonding). Its implementation is most effective when combined with active learning models such as Project-Based Learning (PjBL) and Contextual Teaching and Learning (CTL). This review contributes by identifying the effective configuration of ethnochemistry within active learning, highlighting its holistic impact on motivation, multidimensional engagement, and cultural-scientific literacy, while critically mapping key implementation challenges. Key findings indicate that this approach significantly enhances learning motivation, cognitive achievement, knowledge retention, and student engagement across behavioral, emotional, and cognitive dimensions. Furthermore, ethnochemistry strengthens students’ cultural identity and scientific literacy. However, its implementation faces challenges, including limited standardized teaching materials, the need for teacher capacity building through specific training, and selectivity due to not all chemistry topics being contextually compatible with local wisdom. It is concluded that ethnochemistry is a promising approach to make chemistry learning more relevant and engaging, effectively boosting student motivation and participation in learning activities.